Interaction of ceramic implant materials with immune system - Rafikova, Guzel; Piatnitskaia, Svetlana; Shapovalova, Elena; Chugunov, Svyatoslav; Kireev, Victor; Ialiukhova, Daria; Bilyalov, Azat; Pavlov, Valentin; Kzhyshkowska, Julia (International journal of molecular sciences, 2023)
The immuno-compatibility of implant materials is a key issue for both initial and long-term implant integration. Ceramic implants have several advantages that make them highly promising for long-term medical solutions. These beneficial characteristics include such things as the material availability, possibility to manufacture various shapes and surface structures, osteo-inductivity and osteo-conductivity, low level of corrosion and general biocompatibility. The immuno-compatibility of an implant essentially depends on the interaction with local resident immune cells and, first of all, macrophages. However, in the case of ceramics, these interactions are insufficiently understood and require intensive experimental examinations. Our review summarizes the state of the art in variants of ceramic implants: mechanical properties, different chemical modifications of the basic material, surface structures and modifications, implant shapes and porosity. We collected the available information about the interaction of ceramics with the immune system and highlighted the studies that reported ceramic-specific local or systemic effects on the immune system. We disclosed the gaps in knowledge and outlined the perspectives for the identification to ceramic-specific interactions with the immune system using advanced quantitative technologies. We discussed the approaches for ceramic implant modification and pointed out the need for data integration using mathematic modelling of the multiple ceramic implant characteristics and their contribution for long-term implant bio- and immuno-compatibility.